Deciphering precursor cell dynamics in esophageal preneoplasia via genetic barcoding and single-cell transcriptomics - Jinho Jang; Kyung-Pil Ko; Jie Zhang; Sohee Jun; Jae-Il Park (Proceedings of the National Academy of Sciences, 2025)
Although histologically normal, esophageal preneoplastic cells harbor early genetic alterations and likely exhibit lineage plasticity. However, their origins and trajectories remain unclear. To address this, we combined genetic barcoding with single-cell RNA sequencing to trace the lineage of esophageal preneoplastic cells. We identified a distinct progenitor-like cell population with high plasticity. Through a scoring system, these high-plasticity cells are mapped, revealing their contributions to proliferative and basal cell populations. This approach uncovers molecular markers, including Nfib and Qk , that define these precursor cells, validated by spatial transcriptomics and a Trp53 Cdkn2a Notch1 mouse model. These findings provide critical insights into early tumorigenesis, highlighting the potential of precursor cells as biomarkers for early detection and therapeutic targets of esophageal squamous cell cancer. By elucidating the cellular dynamics underlying esophageal preneoplasia, this research lays the foundation for strategies to prevent malignant progression, offering broader implications for improving cancer diagnostics and treatment approaches.